Tales of the unexpected: the selection of British party leaders since 1963 - Denham, Andrew; Dorey, Peter (Palgrave Macmillan, 2018)
Jeremy Corbyn’s election as Leader of the Labour Party in 2015 stunned observers and practitioners of British politics alike. In this article, we first outline a theoretical framework that purports to explain why political parties operating in parliamentary systems choose the leaders they do. We then examine 32 leadership successions involving five major British parties since 1963, and note that many of these were unexpected, in that they were triggered by unforeseen circumstances, such as the sudden death or resignation of the incumbent. Examining each party in turn, we briefly explain why the winners won and identify at least eight cases (a quarter of our sample) where a candidate widely expected to prevail at the outset was ultimately defeated by a ‘dark horse’, ‘second favourite’ or even ‘rank outsider’. Of these, Corbyn’s election in 2015 was the most unexpected and, consistent with the findings of studies of party leadership conventions in other parliamentary systems, namely Canada and Spain, suggests that ideological and policy concerns are sometimes more important than considerations of party unity and electability, especially when a leadership contest is dominated by party activists.